The clinical study and management of lateral neck masses - Deshpande, Amol Vasantrao; Pothare, Amit Narayan (International Surgery Journal, 2017)
Background: Tumors of neck are especially interesting to surgeons because of complex neck anatomy and difficult differential diagnosis. The aim is to study different type of lateral neck masses excluding thyroid and salivary swellings, there relation with age and se, there clinical features, presentation, and complications, diagnostic modalities and treatment according to the diagnosis and miscellaneous and rare lumps in the neck. Methods: The study was conducted at Shri Vasantrao Naik Government Medical College, Yavatmal, Maharashtra, India from January 2012 to December 2015. In cases of tubercular lympahdenopathy, patients are treated with antitubercular chemotherapy regime DOT’s. In cases of malignant secondaries in neck, patients were offered radical neck dissection, radical radiotherapy or neoadjuvant chemotherapy followed by neck dissection. Results: Total 228 patients are studied. 74.56% were benign and 25.44% were malignant. Most common age group affected was 11-20 years. Malignant lesions were more common after 50 years. Male female ratio was nearly equal. Most common lesion overall was tubercular lymphadenopathy followed by malignant lymph nodes. Conclusions: Lymphadenopathy predominated lateral neck swellings of which tubercular lymphadenopathy found to be commonest followed by malignant secondries. Tubercular infections are common during 1st and 2nd decade, while malignant lesions after 5th decade. FNAC was most common and most effective investigation. Treatment varies according to the cause of lateral neck mass.